Food processing training workshop - Birachi, Eliud; Munthali, Justice; Mugendi, Benson (2024)
In September 2024, the Pan-Africa Bean Research Alliance (PABRA), which is part of the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT), held a focused workshop with the aim of empowering small and medium-sized enterprises (SMEs) to take the lead in adding value to the agribusiness sector in East and Southern Africa. This Newsletter has been prepared with the support of PABRA for the CGIAR Food Systems Accelerator (CFSA) as part of the CGIAR Initiative on Diversification in Eastern and Southern Africa (Ukama Ustawi).